In what ways does social influence affect purchase intention in the case of fitspiration? A Social Influence Theory application - Cheatham, Jacob (2017)
Research on the topic of social influence has offered valuable information to marketers in past and recent years. Numerous scholars focusing on the Social Influence Theory have found the work of Herbert Kelman (1958) as an applicable representation of how consumers are influenced by modern advertising. As an application of the theory, this study investigates the impact of fitspiration advertising on purchase intention by how it influences motivation. Recent studies have documented an increase in interest for fitness and health, with many consumers interacting with new forms of advertising on social media such as fitspiration. Participants were 102 adults aged between 18-25 asked to complete a survey containing 40 questions. Significant exposure to the advertising concept was not distinctively supported to impact purchase intentions by affecting consumer motivation. However, relative to the theory, the results did propose the possibility of influence and inform past research.